PENGARUH LIMBAH CAIR INDUSTRI TAHU TERHADAP KUALITAS AIR SUNGAI BABURA KECAMATAN MEDAN POLONIA (The Disposal Effect of The Waste Water of Tofu Factory to Water Quality Of The Babura River Medan Polonia District) - Sharah Dina; Ternala Alexander Barus; Maragunung Dalimunthe (AQUACOASTMARINE, 2014)
Babura River is one of the three river in Medan.Where this river is already contaminated which is caused by the plastic product disposal, disposal of household waste that flowed trough the trenches, and also the disposal of the waste water of the tofu industry. The purpose of this research is to know more regarding how far the effect of the disposal of the waste water of the tofu industry to the quality of Babura River. This research was conducted in August until September 2013 with determining 3 stations. Which every stations divided into three point for water sampling which is taken 100 m from every station. The physic and chemical parameter that is taken for observed are temperature, brightness of the water, Colour, Turbidity, TSS,TDS,DO, BOD, COD, Nitrate, Phosphate and pH.Based on the result of the research using the storet methode we got total score of the each stations in the amount of -29 in the station 1, -22 in the station 2 and -30 in the stations 3 based on the result we can conclude that the contaminations level from the three stations is categorized as c class contaminations which is contaminated with score -11 up to -30.Keywords: Babura river, Storet methods, waste water from tofu industry